2021
DOI: 10.1002/spp2.1341
|View full text |Cite
|
Sign up to set email alerts
|

A new burnetiid from the middle Permian of Zambia and a reanalysis of burnetiamorph relationships

Abstract: A new taxon of burnetiamorph therapsid, Mobaceras zambeziense gen. et sp. nov., is described on the basis of a partial skull recovered from the lower Madumabisa Mudstone Formation (Guadalupian) of Zambia. This taxon can be distinguished from all previously known burnetiamorphs by its unique cranial boss morphology, including a bulbous nasal boss on a 'stalk' and highly discretized, exaggerated anterior and posterior supraorbital bosses. Burnetiamorph phylogeny has recently become contentious; here, support for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Phylogenetic Position of Isengops Kammerer and Sidor (2021) recently published a comprehensive review of the characters used in most previous analyses of burnetiamorph phylogenetic relationships. Their paper was, in part, a response the results of Day et al (2016), who found unorthodox phylogenetic results markedly at contrast to the majority of those since the initial studies of the group (e.g., Sidor, 2000;Sidor and Welman, 2003;Sidor et al, 2004;Kammerer, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Phylogenetic Position of Isengops Kammerer and Sidor (2021) recently published a comprehensive review of the characters used in most previous analyses of burnetiamorph phylogenetic relationships. Their paper was, in part, a response the results of Day et al (2016), who found unorthodox phylogenetic results markedly at contrast to the majority of those since the initial studies of the group (e.g., Sidor, 2000;Sidor and Welman, 2003;Sidor et al, 2004;Kammerer, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, they found currently recognized burnetiamorphs to be paraphyletic in some analyses, with the middle Permian Bullacephalus and Pachydectes forming a clade with Hipposaurus to the exclusion of other burnetiamorph taxa. Kammerer and Sidor (2021) reanalysis of the Day et al (2016) data set suggested that: (1) some characters could be excluded because they were either parsimony uninformative or strongly tied to ontogenetic status of the specimens under study, (2) some character state attributions were mistaken and were corrected in the revised data matrix, and (3) some characters had to be reformulated in order to better describe and encompass the range of variation seen within the ingroup. After their revisions, the Kammerer and Sidor (2021) resulting data set included 27 characters and 21 operational taxonomic units (all biarmosuchians).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations